Crossing the Rubicon: Debussy and the Eternal Present of the Past - Marion, Gregory (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
This paper proposes that Mikhail Bakhtin's heteroglossia—the process of coming to know one's own language in the language of others—is evident in two of Debussy's compositions from Children's Corner, most directly in "Golliwogg's Cake-Walk" and more subtly in "Serenade for the Doll." In particular, "Serenade" collapses a number of historical horizons—some of these Wagnerian—as Debussy finds his own compositional path. Debussy's approach reflects the obsession La belle Époque had with the past, and moreover with its need to keep the past alive while fashioning a future through the blending of multiple voices.